2023
DOI: 10.21203/rs.3.rs-2553775/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracurricular Activities in Medical Education: An Integrative Literature Review

Abstract: Background: The importance of extracurricular activities (EAs) has been emphasized in medical education. These activities could enhance medical students’ emotional and physical health and afford them developmental opportunities. Despite the growing amount of research related to this theme, few studies review and synthesize the existing literature. This literature review aims to provide an understanding of the educational implications of EAs in medical colleges and constructs an integrated conceptual framework … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…Medical education is often characterised by rigorous schedules and heavy workloads, leaving little time for extracurricular activities such as exercise. [36] Moreover, the high levels of stress associated with medical training might also contribute to a sedentary lifestyle among medical students. [37] It is important to recognize these challenges and address them effectively through targeted interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Medical education is often characterised by rigorous schedules and heavy workloads, leaving little time for extracurricular activities such as exercise. [36] Moreover, the high levels of stress associated with medical training might also contribute to a sedentary lifestyle among medical students. [37] It is important to recognize these challenges and address them effectively through targeted interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Las "actividades extracurriculares" son aquellas que se desarrollan fuera del plan de estudios regular y buscan complementar la formación del estudiante en áreas específicas. Estas actividades, aunque no forman parte del currículo oficial, desempeñan un papel vital en el desarrollo integral de los alumnos (33,34) . De manera específica, y en el ámbito de la investigación, estas actividades buscan fomentar y canalizar el interés de los estudiantes hacia la generación y difusión de conocimiento.…”
Section: Las Actividades Extracurricularesunclassified
“…academic and extracurricular activities in order to improve their work-life balance [21]. On the other hand, some research has shown that medical institutions tend to heavily focus on extracurricular research programs to enhance research competency because medical students have strong interest in developing professionalism through extracurricular research participation [24]. Conversely, this may lead to negative outcomes, such as stress and burnout [25].…”
Section: Plos Onementioning
confidence: 99%